Ekonomi Syariah dan Ekonomi Pancasila Dalam Bingkai Peraturan Hukum Indonesia - Atikah, Ika; Nurrohman, Nurrohman; Mustofa, Mustofa (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This research aims to explain the presence of law, Sharia economics and Pancasila economics based on cooperation by prioritizing humanitarian principles. This research method uses a doctrinal approach with statutory and conceptual approaches. The results of this research are that the presence of law provides a binding and coercive nature for everyone who carries out transactions in Sharia economic activities and the Pancasila economy, so the role of the state as a policymaker is to issue regulations in the form of specific laws with the birth of the Sharia Banking Law, part of sharia economics, and the Cooperative Law, part of the Pancasila economy, as a form of national protection for all Indonesian people.Keywords : Sharia Economic, Pancasila Economic, Regulation